Comparison of building energy demand for hotels, hospitals, and offices in Korea. (1st December 2015) - Chung, Mo; Park, Hwa-Choon
Abstract: Energy demand characteristics were surveyed and measured throughout Korea to establish load models for three types of buildings: hotels, hospitals, and offices. The consumption of electricity and fuel was collected and statistically analysed to establish four types of building loads: electricity, heating, hot water, and cooling energy. The annual, monthly, daily, and hourly patterns of the four load types were derived for the three building types. Key statistical values such as the annual mean, maximum, and minimum values are provided. A procedure is presented to compose building load models as a time series covering the 8760 h of a year by combining daily and hourly patterns. The key features of the load models were compared to better understand the energy consumption characteristics of the three building types. Substantial variations in the magnitudes and patterns were observed among the types of buildings and loads. The load models can be applied to a wide range of problems in building energy system design and planning, including simulations and optimizations of community energy systems. Highlights: We surveyed the energy demands by hotels, hospitals and offices in Korea. We measured energy demand of selected hotels, hospitals and offices. Hourly energy demand models for a year were derived for those buildings. Energy demand characteristics of the building types were compared.